Asymmetric macro-financial spillovers - Kristina Bluwstein (Sveriges Riksbank, 2017)
The 2008 financial crisis has shown that financial busts can influence the real economy. However, there is less evidence to suggest that the same holds for financial booms. Using a Markov-Switching vector autoregressive model and euro area data, I show that financial booms tend to be less procyclical than financial busts. To identify the sources of asymmetry, I estimate a non-linear DSGE model with a heterogeneous banking sector and an occasionally binding borrowing constraint. The model matches the key features of the data and shows that the borrowers' balance sheet channel accounts for the asymmetry in the macro-financial linkages. The muted macro-financial transmission during financial booms can be exploited for macroprudential policies. By comparing capital buffer rules with monetary policy "leaning-against- the-wind" rules, I find that countercyclical capital buffers improve welfare.
Keywords: E44; E58; E52; 330; Macro-financial linkages; non-linearities; Markov-Switching VAR; credit channel; occasionally binding constraints; DSGE; macroprudential policy; leaning-against-the-wind policy